Synaptic activity protects neurons against calcium-mediated oxidation and contraction of mitochondria during excitotoxicity - Depp, Constanze; Bas Orth, Carlos; Hellwig, Andrea; Bading, Hilmar (Antioxidants & redox signaling, 2018)
Aims: Excitotoxicity triggered by extrasynaptic N-methyl-d-aspartate-type glutamate receptors has been implicated in many neurodegenerative conditions, including Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis, and stroke. Mitochondrial calcium overload leading to mitochondrial dysfunction represents an early event in excitotoxicity. Neurons are rendered resistant to excitotoxicity by previous periods of synaptic activity that activates a nuclear calcium-driven neuroprotective gene program. This process, termed acquired neuroprotection, involves transcriptional repression of the mitochondrial calcium uniporter leading to a reduction in excitotoxcity-associated mitochondrial calcium load. As mitochondrial calcium and the production of reactive oxygen species may be linked, we monitored excitotoxicity-associated changes in the mitochondrial redox status using the ratiometric glutathione redox potential indicator, glutaredoxin 1 (GRX1)-redox-sensitive green fluorescent protein (roGFP)2, targeted to the mitochondrial matrix. Aim of this study was to investigate if suppression of oxidative stress underlies mitoprotection afforded by synaptic activity.Results: We found that synaptic activity protects primary rat hippocampal neurons against acute excitotoxicity-induced mitochondrial oxidative stress and mitochondrial contraction associated with it. Downregulation of the mitochondrial uniporter by genetic means mimics the protective effect of synaptic activity on mitochondrial redox status. These findings indicate that oxidative stress acts downstream of mitochondrial calcium overload in excitotoxicity.Innovation and Conclusion: We established mito-GRX1-roGFP2 as a reliable and sensitive tool to monitor rapid redox changes in mitochondria during excitotoxicity. Our results highlight the importance of developing means of blocking mitochondrial calcium overload for therapeutic targeting of oxidative stress and mitochondrial dysfunction in neurodegenerative diseases.